Working the Mississippi : Two Centuries of Life on the River - Stepenoff, Bonnie, 1949- (Book collections on Project MUSE., 2015)
The Mississippi River occupies a sacred place in American culture and mythology. Often called The Father of Rivers, it winds through American life in equal measure as a symbol and as a topographic feature. To the people who know it best, the river is life and a livelihood. River boatmen working the wide Mississippi are never far from land. Even in the dark, they can smell plants and animals and hear people on the banks and wharves. Bonnie Stepenoff takes readers on a cruise through history, showing how workers from St. Louis to Memphis changed the river and were in turn changed by it. Each chapter of this fast-moving narrative focuses on representative workers: captains and pilots, gamblers and musicians, cooks and craftsmen. Readers will find workers who are themselves part of the country's mythology from Mark Twain and anti-slavery crusader William Wells Brown to musicians Fate Marable and Louis Armstrong.